Ovarian remnant syndrome in small animals - Oliveira, Kellen de Sousa [UNESP]; Machado Silva, Marco Augusto [UNESP]; Brun, Mauricio Veloso; Perez-Gutierrez, Jose Felix; Toniollo, Gilson Hélio [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The ovarian remnant syndrome (ORS) is an iatrogenic disorder in bitches and queens, which is characterized by recurrence of estrus following surgical spay, due to the presence of a piece of ovarian tissue within the abdominal cavity. In most cases, the remnant ovary is found in the right ovarian pedicle, due to its topographic position, deeper and more cranial than the left ovary. The main clinical signs of ORS in small animals are the heat behavior and the presence of vaginal swelling/secretion, especially in canines. The diagnosis should be performed by means of vaginal cytology when attraction of males is detected, serum estrogen and progesterone levels and/or by challenging test with GnRH or hCG administration. However, vaginal citology is the most suitable and less expensive diagnostic tool. Nowadays the treatment of choice is a new laparotomy or laparoscopy, followed by removal of the remnant ovarian tissue. The surgical treatment has more chances of success if it is performed in the diestrus (i.e., between 15 and 60 days after the detection of attraction of males). Furthermore, a careful and accurate surgical procedure aided by advanced visualization techniques during ovariohysterectomy or ovariectomy is the best way to prevent ORS in companion animals.
Keywords: Partial ovarian spay; recurrent estrus; bitches; queens